Trauma societies and their characteristics: Between evolution and revolution - Toshchenko, Zhan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The development of civilization at the present stage is faced with a phenomenon that is still poorly studied and little known, which we call the trauma of society. The fact is that significant, special and specific events are taking place in the world that cannot be defined and qualified in the old terms of evolution and revolution, which describe and reflect the changes that are taking place. Currently, there are 53 states that, according to the World Bank, that have been or are in a state of chaotic, unbalanced and turbulent development for a long period.
Keywords: civilization; revolution; evolution; trauma; development; social implications